Mass fluctuation in breeding females, males, and helpers of the Florida scrub-jay Aphelocoma coerulescens - Marco Cucco; Reed Bowman (PeerJ, 2018)
Much evidence suggests that birds actively regulate their body mass reserves relative to their energy needs. Energy requirements during reproduction may differ in relation to sex-specific behavioural roles or, in the case of cooperative breeders, breeders relative to helpers. We measured body mass of free-living Florida scrub-jays throughout the nesting season by training them to land on an electronic balance. Jays exhibited a pattern of diurnal linear mass gain, from morning to afternoon. Day-to-day mass fluctuations, defined as the difference between mass on two consecutive days, were small (>80% were within 2 g, less than 3% of the mass of an adult bird) for all classes of jays: female breeders, male breeders and prebreeding helpers. The jays, which live in subtropical south-central Florida, did not exhibit changes in day-to-day mass fluctuation relative to weather or climate variables or calendar date. Day-to-day mass fluctuations influenced mass fluctuation between the following third and fourth days. These changes were usually compensatory, indicating that jays are able to regulate their body mass on a short-term basis, despite strong differences in their roles in reproduction. During reproduction, jays have a relatively predictable and abundant food supply, thus the appropriate strategy may be to maintain a stable body mass that balances some energy reserves against maintaining a low body mass for efficient flight, as required during reproduction.